Responsiveness of time and cost-efficient monitoring measures on triathlon training: a call for individualized training monitoring - Schäfer Olstad, B.; Borgen-Johansen, M.; Garthe, I.; Paulsen, G. (Journal of Athletic Enhancement, 2019)
Objective: We aimed to assess the responsiveness of monitoring measures on cumulative training from the previous 1 up to 7 days in elite triathletes.